ABOUT AIR QUALITY AND PUBLIC HEALTH IN THE CITY OF TASHKENT - Madraim Khasanovich Sarikulov (Western European Studies, 2024)
This article discusses the issues of air pollution, in the context of the air quality index and public health in the city of Tashkent and the Tashkent region at the present stage. The problem of atmospheric air pollution has been studied and a comparative analysis of air quality index indicators has been carried out. Issues of public health in the city of Tashkent, taking into account the level and quality of air, were also considered.
Keywords: Air pollution; ambient air quality; crop yield